Rebuilding Birth: Towards Humanized and Respectful Obstetric Care - Silveira, Déborah Suelen Goes; Ventura, Renata de Souza; Botelho, Rayane Martins (JRG Journal of Academic Studies, 2023)
This work is an integrative literature review aimed at providing a comprehensive overview of obstetric violence in Brazil and the role of nursing in this situation, to reflect on the importance of a humane medical team in the cesarean section process in the surgical center. The study allowed for an understanding that the moment of childbirth is full of vulnerability and fear, as it is the parent’s first contact with the baby outside the womb. In the case of surgical intervention, there is also a risk of complications and even the need to address complications that may have arisen during childbirth. In this perspective, the present work presents an analysis of the childbirth moment, where power dynamics between the medical team and the mother in the hospital setting highlight the obstetric violence experienced during cesarean delivery. To achieve this, the methodology employed in this study was a literature review and exploratory research, where through bibliographic inquiries, an understanding of the object of this study, i.e., obstetric violence, was possible. It was concluded that this hierarchical power relationship results in obstetric violence.